How Much Proportionality in Degressive Proportionality: The Case of Allocating Seats in the European Parliament Among Member States of the European Union - Arkadiusz MACIUK (Communications of International Proceedings, 2025)
In the case of cooperation of many entities, smaller entities are at risk of being dominated by larger entities. In order to limit this potential domination when choosing decision-makers setting the rules of this cooperation, the principle of degressive proportionality can be applied. Equal allocation favors the agents with small claims, proportional allocation is more favorable for the agents with larger claims, whereas degressive proportionality is supposed to be a compromise between these two apportionments. A classic example of such allocation is apportionment of mandates in the European Parliament among individual member states of the European Union. This paper examined the proportions between equal and proportional allocations in consecutive terms of the European Parliament in the perspective of 1979-2024. For this purpose, the Loosemary-Hanby index and the related Schutz index are used. The research shows that while the proportional component of these allocations has always dominated over the equal component, the level of this dominance is constantly decreasing. However, the imbalance between population allocation and parliamentary seat allocation continues to grow, but the rate of growth has slowed significantly since 2004. The properties of Loosemore-Hanby index were also described to indicate that this disproportionality index can also be considered a measure of inequality in respect of each of two analyzed allocations separately.
Keywords: domination; degressive proportionality; European Parliament; Loosemore-Hanby index.